Two phase tillage: quick method for crop production in saline soils - Li, Weiqiang; Liu, Xiaojing; Qiao, Hailong; Sun, Jialing; Duan, Deyu (MTT, 2005)
High soil salinity restricts crop growth in saline soil area. The traditional way for crop production in that area is to reclaim by water engineering method, i.e. irrigation. However in coastal saline area around Bohai Sea due to fresh water shortage, low elevation and high groundwater table, it is difficult to reclaim the saline soils by that method. In this paper we introduce a method for crop production in saline soils based on the local climate, soil salt dynamics and the characteristics of crop growth. The key technology is to form two phases in soil profile, i.e. to form a 5 cm straw layer below 20 30 cm of soil surface. The role of the straw layer is to keep the salt moving up to root zone or soil surface. Results show that when winter wheat started to grow in early spring, the surface soil salinity is 2.8 and 17 ms/dm in treatment and CK respectively. At the same stage, 80% of seedlings was died in CK and almost no died in treatment. Finally the seeds yield was 6270 kg/ha and 1290 kg/ha in treatment and CK respectively.
Keywords: Ys; two phase tillage; crop production; saline soils